JARGON DALAM TRANSAKSI JUAL BELI PEDAGANG TANAMAN DI LUBUK MINTURUN KECAMATAN KOTO TANGAH PADANG SUMATERA BARAT - Silvia, Mega; Ermanto, Ermanto; Juita, Novia (Jurnal Bahasa dan Sastra, 2018)
The research was done because of the heterogeneous of Indonesian society which create the varieties of language insed in daily life. It is known as jargon. Let’s see the jargon used by plant sellers in Lubuk Minturun subdistrict Koto Tangah Padang, West Sumatera in their daily activities, especially in doing transaction of trading. They have special vocabularies called jargon. The purpose of this research is (1) to describe the form jargon used by plant sellers in Lubuk Minturun sub district Koto Tangah Padang West Sumatera. (2) To describe the meaning of jargon used by plant sellers in Lubuk Minturun subdistrict Koto Tangah Padang, West Sumatera. This research is a qualitative research that produces a descriptive data. It means the data analyzed and the result of the analysis is in a descriptive form, not in form of numeral of the efficiency of the relationship between variables. In this research, the data was taken from the daily conversation among the plant sellers in Lubuk Minturun by using listen method (record based technique). Based on the research about jargon in the trading transaction among the plant sellers in Lubuk Minturun sub district Koto Tangah Padang, West Sumatera, jargon can be classified into form and meaning. (1) Form, it can be words, phrases, or clauses. The word in jargon can be verbs, nouns, or adjectives. Phrases in jargon can be verb phrases, noun phrases, or adjective phrases. (2) Meaning, it has the lexical meaning and contextual meaning.Keywords : Jargon, Sellers, Plant, Trading transaction, Lubuk Minturun.